Avaliação do uso do teste do degrau de três minutos na identificação de exacerbação pulmonar em crianças e adolescentes com fibrose cística - Costa, Gisele Apolinário da (2022)
Introduction: Cystic Fibrosis (CF) is a chronic disease that affects the respiratory system. One of the causes of patient morbidity and mortality is a pulmonary exacerbation, which is evaluated by the use of specific scores. However, there is no consensus on the best form of diagnosis. Considering that the three-minute step test (TD3) is a test of easy application and good reproducibility, it may be useful in identifying pulmonary exacerbations in these patients. Objective: To evaluate the use of TD3 in the identification of pulmonary exacerbation in children and adolescents with CF. Methods: Cross-sectional study in which patients aged six years and older with CF confirmed by genetic testing were included. Those patients who had any limitation that prevented the realization of the TD3 were excluded. The presence of pulmonary exacerbation was assessed using the Kanga score, and quadriceps muscle strength using dynamometry. Afterwards, the TD3 was performed and the patient went up and down a step with a height of 15 cm for three minutes. Heart rate (HR), peripheral oxygen saturation (SpO2) and sensation of dyspnea and lower limb fatigue were measured using the modified Borg scale, before and after the test. The values obtained were compared between exacerbated and non-exacerbated patients and the sensitivity/specificity calculated. Results: Sixty-two patients with a mean age of 11.1±4.25 years were included. Pulmonary function was found to be reduced and the mean Kanga score in the sample was around 16, with a score above 20, which is considered moderate/severe pulmonary exacerbation, achieved by at least a quarter of the patients. Kanga score correlated with age, FEV1, 1-minute recovery HR, SpO2 after TD3, and 1-minute recovery SpO2. When comparing patients with the highest and lowest scores on the Kanga score, age, resting HR and 1-minute recovery HR were significantly higher in the group with the highest scores. On the other hand, FEV1, SpO2 at rest, SpO2 after TD3 and SpO2 after 1 minute of recovery were significantly lower in the group with the highest score. The analysis of the ROC curve showed that the HR recovery after 1 minute of performing the TD3 was the best variable to predict pulmonary exacerbation, with good sensitivity and specificity for a cut-off value of 111 bpm. Conclusion: The TD3 demonstrated good sensitivity in detecting moderate/severe pulmonary exacerbation in children and adolescents with CF and may be considered as an additional method to assist in the evaluation and follow-up of these patients.